Contribution of Stretch to the Change of Activation Properties of Muscle Fibers in the Diaphragm at the Transition from Fetal to Neonatal Life - Cannata, David J.; Crossley, Kelly J.; Barclay, Chris J.; Walker, David; West, Jan M. (Frontiers in Physiology, 2011)
The transition from fetal to postnatal life involves clearance of liquid from the lung and airways, and rapid formation of a functional residual capacity. Despite the importance of the diaphragm in this process, the impact on the mechanical and functional activity changes of its muscle fibers is not known. This study determined the contractile characteristics of individual ‘skinned’ diaphragm fibers from 70 days gestation to adulthood in sheep, and determined the impact of the transition from the in utero fetal status to (a), spontaneous air breathing; or (b) mechanical ventilation - on passive tension and calcium- and strontium-activated properties of single fibers isolated from the diaphragm. Based on differential sensitivity to the divalent ions calcium (Ca2+) and strontium (Sr2+), all fibers in the fetal diaphragm were classified as ‘fast’, whereas fibers from the adult diaphragm exhibited a ‘hybrid’ phenotype wherein both ‘fast’ and ‘slow’ characteristics were present within each single fiber. Transition to the hybrid phenotype occurred at birth, was evident after 40 mins of spontaneous breathing, and could be induced by mechanical stretch of diaphragm fibers from near term foetuses ( 147 days gestation). Applied stretch of fibers, achieved either by physical stretch of isolated fibres or mechanical ventilation of the fetus, significantly increased sensitivity to Ca2+ and Sr2+, maximum force generating capacity, and decreased passive tension in near-term and preterm fetuses. However, only fibers from near-term fetuses displayed a complete transition to a ‘hybrid’ activation profile., These findings suggest that activation properties of the diaphragm are changed by transition from a liquid to air-filled lung at birth, and that stretch induces physical changes of proteins determining the activation and elastic properties of the diaphragm. These changes may allow the diaphragm to meet the increased mechanical demands of breathing immediately after birth.